Value Education through Jeevan Vidya - Mali, M. S. (Journal of Engineering Education Transformations, 2008)
Technology is only a means to achieve what is 'considered valuable', in an effective and efficient manner. It is not within the scope of technology, to decide what is valuable. This decision lies outside its scope. It is important to find out what is that subject or thought that decides on "what is valuable?". Without this decision, technology is aimless, direction less and therefore can be put to any use-constructive or destructive.